Can nursing epistemology embrace p‐values?. (15th February 2017) - Ou, Christine H. K.; Hall, Wendy A.; Thorne, Sally E.
Abstract: The use of correlational probability values ( p ‐values) as a means of evaluating evidence in nursing and health care has largely been accepted uncritically. There are reasons to be concerned about an uncritical adherence to the use of significance testing, which has been located in the natural science paradigm. p ‐values have served in hypothesis and statistical testing, such as in randomized controlled trials and meta‐analyses to support what has been portrayed as the highest levels of evidence in the framework of evidence‐based practice. Nursing has been minimally involved in the rich debate about the controversies of treating significance testing as evidentiary in the health and social sciences. In this paper, we join the dialogue by examining how and why this statistical mechanism has become entrenched as the gold standard for determining what constitutes legitimate scientific knowledge in the postpositivistic paradigm. We argue that nursing needs to critically reflect on the limitations associated with this tool of the evidence‐based movement, given the complexities and contextual factors that are inherent to nursing epistemology. Such reflection will inform our thinking about what constitutes substantive knowledge for the nursing discipline.